Learning Through Uncertainty: Emotional Coping Practices of Mangosteen Farmers as Informal Education Processes - Nurul Hikmah; Muhammad Fedryansyah; Dyana Chusnulitta Jatnika (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study examines emotional coping strategies among mangosteen farmers who face persistent uncertainty due to climate variability, unstable market prices, and long production cycles. Emotional coping is conceptualized as a set of internal processes that enable farmers to regulate stress, maintain psychological stability, and sustain their livelihoods. Using a qualitative approach, the study identifies four dominant coping patterns: acceptance, spiritual coping, social emotional support, and cognitive reframing. Each strategy is analyzed in depth to understand its function, process, and impact on resilience. The findings reveal that emotional coping is not passive but constitutes an active adaptive mechanism that allows farmers to endure uncertainty over time. The study contributes by providing a detailed conceptualization of emotional coping in agricultural contexts, highlighting its central role in sustaining farmer resilience.